1992
DOI: 10.1530/acta.0.1270072
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid hormones on mitochondrial oxygen consumption in brown adipose tissue and heart from cold-exposed hypothyroid rats

Abstract: The present work measured brown adipose tissue and heart mitochondrial oxygen consumption in hypothyroid rats treated with replacement doses of T3, T4 or T4 plus iopanoic acid and kept at 4°C for 24 h. Heart oxygen consumption in normal, untreated hypothyroid and T4-treated hypothyroid rats was unaffected by cold exposure. In rats treated with T4 plus iopanoic acid, rates of oxygen consumption were normal in those maintained at 4°C as well as in those kept at room temperature, despite serum T3 concentration be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In fact, Table 1 shows that the ␣-GPD activity in the BAT of hypothyroid rats was Ͼ230 times higher than that in liver, which accounts for the enhanced substrate oxidations in BAT mitochondria. In a previous study (6), BAT ␣-GPD activity was 15-fold that in heart, and it was not affected by changes in temperature or thyroid hormones.…”
Section: Changes In ␣-Gpd Activitymentioning
confidence: 55%
See 1 more Smart Citation
“…In fact, Table 1 shows that the ␣-GPD activity in the BAT of hypothyroid rats was Ͼ230 times higher than that in liver, which accounts for the enhanced substrate oxidations in BAT mitochondria. In a previous study (6), BAT ␣-GPD activity was 15-fold that in heart, and it was not affected by changes in temperature or thyroid hormones.…”
Section: Changes In ␣-Gpd Activitymentioning
confidence: 55%
“…This degree of receptor occupancy could not be reached in cold-exposed, T 3 -treated hypothyroid rats even after the administration of Ͼ15 times the physiological T 3 replacement and extremely hyperthyroid levels of serum T 3 (3). This phenomenon explains the development of hypothermia during cold exposure of hypothyroid rats treated with physiological amounts of T 3 (6,7). The foregoing data are consistent with the fact that thyroid hormone production in hypothyroid rats was nil or sufficiently low that it resulted in a deep hypothyroid state.…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, other factors, exhibiting different serum concentrations in functional and experimental hyperthyroidism, should be involved in mitochondrial proliferation associated to cold exposure. Unlike cold exposure, T 3 administration strongly decreases serum levels of T 4 , (Venditti et al, 2006a), which has been reported to have intrinsic biological activity in the cold (Cageao et al, 1992). Plasma levels of catecholamines, which are not modified in altered thyroid states (Stoffer et al, 1973), remarkably increase during cold exposure (Storm et al, 1981).…”
Section: Introductionmentioning
confidence: 98%
“…However, only data concerning changes in glutathione peroxidase activity and mitochondrial protein content favour the idea that dissimilarities in effects of cold exposure and T 3 treatment could depend on differences in serum levels of T 4 . the cold (Cageao et al, 1992). Thus, it is possible that T 4 contributes to some changes underlying tissue thermogenesis and oxidative stress associated with cold exposure.…”
Section: Introductionmentioning
confidence: 99%